Birthweight, genetic risk, and gastrointestinal cancer incidence: a prospective cohort study. (31st December 2023) - Long, Lu; He, Heng; Shen, Qian; Peng, Hongxia; Zhou, Xiaorui; Wang, Haoxue; Zhang, Shanshan; Qin, Shifan; Lu, Zequn; Zhu, Ying; Tian, Jianbo; Chang, Jiang; et al.
Abstract: Background: The epidemiologic studies investigating the association of birthweight and genetic factors with gastrointestinal cancer remain scarce. The study aimed to prospectively assess the interactions and joint effects of birthweight and genetic risk levels on gastrointestinal cancer incidence in adulthood. Methods: A total of 254, 997 participants were included in the UK Biobank study. We used multivariate restricted cubic splines and Cox regression models to estimate the hazard ratios (HRs) and 95% confidential intervals (CI) for the association between birthweight and gastrointestinal cancer risk, then constructed a polygenic risk score (PRS) to assess its interaction and joint effect with birthweight on the development of gastrointestinal cancer. Results: We documented 2512 incident cases during a median follow-up of 8.88 years. Compare with participants reporting a normal birthweight (2.5–4.5 kg), multivariable-adjusted HR of gastrointestinal cancer incidence for participants with high birthweight (≥4.5 kg) was 1.17 (95%CI: 1.01–1.36). Such association was remarkably observed in pancreatic cancer, with an HR of 1.82 (95%CI: 1.26–2.64). No statistically significant association was observed between low birth weight and gastrointestinal cancers. Participants with high birthweight and high PRS had the highest risk of gastrointestinal cancer (HR: 2.95, 95%CI: 2.19–3.96). Conclusion: Our findings highlight that high birthweight is associated with a higher incidence of gastrointestinal cancer, especially for pancreatic cancer. Benefits would be obtained from birthweight control, particularly for individuals with a high genetic risk. KEY MESSAGES: The epidemiologic studies investigating the association of birthweight and genetic factors with gastrointestinal cancer remain scarce. This cohort study of 254, 997 adults in the United Kingdom found an association of high birthweight with the incidence of gastrointestinal cancer, especially for pancreatic cancer, and also found that participants with high birthweight and high polygenic risk score had the highest risk of gastrointestinal cancer. Our data suggests a possible effect of in utero or early life exposures on adulthood gastrointestinal cancer, especially for those with a high genetic risk.